Representations of Christ in Christian Skaldic Poetry - Cheadle, RE (UCL (University College London), 2015)
This thesis aims to demonstrate that, through use of literary genre, vocabulary, and emphasis of detail, the authors of Christian skaldic verse in the twelfth to fifteenth centuries continually reshaped a specific set of representations for Christ to suit each poem’s individual purpose, its audience, and the literary tastes of the periods in which they were written. In order to show how Christ’s portrayal changes over time and according to each poem’s overarching purpose, I have selected the following five Christian skaldic poems and made each the focus of a chapter: Einarr Skúlason’s Geisli, Gamli kanóki’s Harmsól, and the anonymously-composed poems Leiðarvísan, Líknarbraut, and Lilja. Within each chapter I provide an overview of the poem, selecting stanzas that highlight features of Christ that are prevalent or striking in some way, and analyse how these representations not only influence the poem itself, but also shape perceptions of Christ’s relationship with humanity. Each chapter leads to an overall consideration both of the image of Christ as this has been represented, and of the degree to which this has been influenced by biblical and patristic writings, Old Norse literature and culture, or by a combination of these elements. In the concluding chapter I identify the prevailing representations of Christ throughout these five poems, dividing these characterisations into five categories: Christ as Warrior Chieftain, as Healer and Abundant Nourisher, as Legal Authority, as Beguiler, and as Light. I assess the changing importance of each of these representations over time and in these poems, in order to enable a better understanding of the changing images of Christ in the medieval skaldic corpus and how these may reflect locally specific perceptions of Christ.